Helping student-athletes learn to self-regulate to alleviate burnout: a multiple case study showcasing their challenging but altering experiences - Dubuc-Charbonneau, N.; Durand-Bush, N. (Journal of Quantitative Analysis in Sports, 2018)
A multiple case study approach was used to investigate how four university student-athletes learned to self-regulate by taking part in an individual season-long intervention designed to reduce stress and burnout symptoms. A male hockey player, female fencer, male swimmer and female basketball player met the initial selection criteria of scoring 3.0 or higher on two of the three subscales of the Athlete Burnout Questionnaire. Pre- and post-intervention interviews as well as seven to nine bi-weekly intervention sessions were conducted with each participant. All data were transcribed verbatim and subjected to a content analysis, subsequent to which narratives were created to depict each student-athlete`s unique experiences throughout the intervention. Through a tailored educational approach, these student-athletes learned to develop and implement various self-regulation strategies in order to manage the multiple demands and challenges (e.g. injuries, autonomy-depleting coaching behaviours, amotivation toward school, excessive drinking, distracting social media) they faced throughout their season. The most commonly used strategies included goal-setting, time and task management, self-monitoring via daily `check-ins` and self-reflection through journaling. Interestingly, prior to this study, two of the student-athletes had previously dropped out of their sport due to burnout but subsequently returned, and one was contemplating quitting at the time of the study. However, all four of them reported post-intervention that with reduced stress and burnout symptoms, and more quality performances and well-being, they intended to continue playing their sport the following year.